Evaluación de las tierras del Departamento Comandante Fernández para el cultivo del algarrobo blanco - Lopez, Astor Emilio; Kees, Sebastian Miguel; Roldan, Maria Florencia; Goytia, Silvia Yanina; Zurita, Juan Jose (Asociación Argentina Ciencia del Suelo (AACS), 2020)
Póster